2012
DOI: 10.1016/j.dnarep.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease 1 (Exo1) is required for activating response to SN1 DNA methylating agents

Abstract: SN1 DNA methylating agents are genotoxic agents that methylate numerous nucleophilic centers within DNA including the O6 position of guanine (O6meG). Methylation of this extracyclic oxygen forces mispairing with thymine during DNA replication. The mismatch repair (MMR) system recognizes these O6meG:T mispairs and is required to activate DNA damage response (DDR). Exonuclease I (EXO1) is a key component of MMR by resecting the damaged strand; however, whether EXO1 is required to activate MMR-dependent DDR remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Izumchenko et al [49] showed in vitro and most recently Schaetzlein et al [50] showed in vivo that the catalytic nuclease function of Exo1 may not be necessary for its role in MMR [49,50]. In fact it has been proposed that the structural component of Exo1 may serve as a docking site or play a scaffolding role in the formation of protein complexes including additional nucleases in MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Izumchenko et al [49] showed in vitro and most recently Schaetzlein et al [50] showed in vivo that the catalytic nuclease function of Exo1 may not be necessary for its role in MMR [49,50]. In fact it has been proposed that the structural component of Exo1 may serve as a docking site or play a scaffolding role in the formation of protein complexes including additional nucleases in MMR.…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae in which it is hypothesized that EXO1 interacts with MutS and/or MutL homologues to promote the stability of protein complexes [85,86]. Although an EXO1-MSH2/MLH1 interaction at physiological protein levels is not detected, ectopic expression of a nuclease-dead EXO1 [JL6] construct in MEF's in which endogenous EXO1 is absent restores a MSH2-CHK1 interaction and MNNG sensitivity [87]. A homozygous knock-in mouse harboring the Exo1-E109IK mutation is MMR-proficient but corresponding embryonic fibroblasts resemble those from Exo1 null strains with regard to loss of apoptotic signaling in response to various DNA damaging agents [74,84] The EXO1 E1091K mutant protein has subsequently been shown to be catalytically competent for excision suggesting that the loss of the DDR could be attributable to an as yet undefined structural role for Exo1 in this pathway [88,89].…”
Section: Dna Methylation and The Ddrmentioning
confidence: 99%
“…γH2AX focus staining. The phosphorylation of histone H2AX was used as a marker of DNA double-strand breaks with slight modifications (14). MG-63 and U-2OS cells (1x10 5 ) were seeded onto 6-well culture plates and treated with 0, 25, 50 and 100 µM of ginsenoside Rg3 and 20 µM MNNG for 24 h. Human fibroblasts were treated with ginsenoside Rg3 (50 mM) and MNNG (20 mM) for 24 h. After treatment, the cells were fixed in 4% paraformaldehyde for 15 min, washed with PBST (PBS buffer pH 7.4 and 0.1% Tween-20), and permeabilized in 1% Triton X-100 for 30 min.…”
Section: Chemicalsmentioning
confidence: 99%
“…Previous research has shown that MNNG can induce the apoptosis of fibroblasts (14). Flow cytometry and the DNA ladder assay were used to detect the ability of ginsenoside Rg3 to protect against MNNG-induced apoptosis in human fibroblasts.…”
mentioning
confidence: 99%